FINANCIAL RISK MANAGEMENT STRATEGIES IN DEALING WITH FOREIGN EXCHANGE RATE FLUCTUATIONS - Loso Judijanto; Nurussama; Rina Apriliani (CV. Adiba Aisha Amira, 2024)
Changes in foreign exchange (forex) rates have a significant impact on the finances of companies that operate internationally. Exchange rate fluctuations can affect profitability, operating costs, and the value of overseas assets, placing pressure on a company's financial stability. This research investigates various financial risk management strategies that can be used by companies to protect themselves from this volatility. The research method used was a literature review. The research found that derivatives, when used appropriately, can significantly reduce the risks associated with exchange rate fluctuations. However, this strategy requires a deep understanding of financial instruments and the forex market, as well as expertise in financial risk management. In addition, the study identified that currency diversification and currency matching are important approaches in risk mitigation that not only protect companies from forex market uncertainties but also help in maintaining liquidity. Another critical factor is the cooperative relationship with international banks that can provide valuable insights and customized solutions for forex risk management.